After the Storm: Inter-disciplinary Dialogic Discourses With a Post-Fishing Community - Stephenson, Carol; MacPherson, Fiona (Frontiers in Sociology, 2020)
This paper is a critical evaluation of a unique approach to working with disadvantaged communities, which involves inter-disciplinary collaboration between an Applied Theater (AT) director and a sociologist. The application of the approach, in a community disadvantaged by the loss of industry, provides the case study basis for the evaluation. Between 2014 and 2017 community participants from Eyemouth, southeast Scotland, worked with an artistic team led by director Fiona MacPherson1, and a sociologist, Carol Stephenson, to develop a creative performance of the town's fishing disaster of 1881. This inter-disciplinary project was facilitated through dialogic discourses between community participants, AT director and sociologist in which the equalization of relationships, meaning-making and active listening were established as shared values and processes. The paper makes four claims. Firstly, sociological observation of the negotiation of the creative process revealed previously hidden and nuanced social interactions, which could later be examined in greater detail with the AT director and in focus group discussions with community participants. Second, the use of dialogic discourses in the critical appraisal of AT practice by the sociologist ultimately enabled the inter-disciplinary sharing of practice, ideas and theories that were mutually beneficial. Third, the creative process revealed insights into the lived experience of post-industrial communities and enabled public sociology discourse, which ultimately prompted social activism within the case study community. Last, while the inter-disciplinary approach is labor intensive and demands high levels of commitment to the shared values associated with dialogic discourses, it provides a new and innovative way of working with, and for, disadvantaged communities.